2022
DOI: 10.1155/2022/9309074
|View full text |Cite
|
Sign up to set email alerts
|

Progress and Prospects of Research on Public Services in Sports in China: Analysis in the Context of Bibliometric Ecological Civilization and Social Networks

Abstract: In order to better understand the current situation of Chinese public sports, this paper studies Chinese public sports. According to SATI3.2 statistics, 71 newsletters have published a total of 903 articles, of which 40 newsletters have one article, 19.7% of the newsletters have 2–9 books, and 17 magazines have more than 10 issues. The results show that by measuring data, we can better understand the current state of China’s public services. This paper uses the method of bibliometric analysis to sort out and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…To date, various studies of sports park accessibility have been reported. For instance, Zhong et al analyzed the shortcomings of the current policies on sports parks in China on the basis of the policy models in Japan and proposed several solutions to policy optimization, including control of construction scale, refining of licensing procedures, promotion of social participation, and development of relevant standards [11].…”
Section: Introductionmentioning
confidence: 99%
“…To date, various studies of sports park accessibility have been reported. For instance, Zhong et al analyzed the shortcomings of the current policies on sports parks in China on the basis of the policy models in Japan and proposed several solutions to policy optimization, including control of construction scale, refining of licensing procedures, promotion of social participation, and development of relevant standards [11].…”
Section: Introductionmentioning
confidence: 99%